RECTIFYING THE UNDERSTANDING AGAINST THE CONCEPT OF ‘ADALAH AL-SAHABAH - Mutiullah, Muhammad (Al'Adalah, 2023)
This research attempts to rectify the concept of 'adalah al-sahabah. There is some agreement among Islamic scholars, especially among the hadith reviewers, that all the Prophet’s Companions were fair. An additional agreement arose from that agreement that it was not permissible to criticize the integrity and characters of the Prophet's Companions as hadith narrators. However, some Companions are presumed to have committed unsavory and inappropriate actions. So, defending this argument becomes problematic; even the Qur'an and Hadith describe some as hypocritical and wicked. This article aims to unravel this problem by rectifying the concept of 'adalah al-sahabah and considering a historical approach in the 1st-9th H centuries related to the Companions' position as hadith transmission. Islamic scholars debate the concept of 'adalah al-sahabah, and there are limitations to understanding a theoretical review of Companions. The study results revealed that not all people who lived during the time of the Prophet can be called the Prophet's Companions. If all of them were called companions and there was no strictness in categorizing the concept rigorously, it would cause polemics among Islamic scholars. The narrator in transmission hadith must be guaranteed fairness according to credibility and contradicting the essential concept of fairness ('adalah) or its companion (al-sahabah). Therefore, the notion of 'adalah al-sahabah should not be seen in general but in a particular context of hadith transmission. However, constant discussion of historical facts is necessary. It opens up the possibility of new findings regarding the selection of authentic hadith narrators based on the concept of 'adalah al-sahabah.